Multicentric Registry Study on Epidemiological and Biological Disease Profile as Well as Clinical Outcome in Patients with Low-Grade Gliomas: The LoG-Glio Project - Pala, Andrej; Nadji-Ohl, Minou; Faust, Katharina; Rückriegel, Stefan; Roder, Constantin; von der Brelie, Christian; Forster, Marie-Therese; Löbel, Franziska; Schommer, Stefan; Löhr, Mario; Renovanz, Mirjam; Grübel, Nadja; Rothenbacher, Dietrich; König, Ralph; Engelke, Jens; Schmitz, Bernd; Wirtz, Christian Rainer; Ringel, Florian; Senft, Christian; Rohde, Veit; Tatagiba, Marcos; Ernestus, Ralf Ingo; Vajkoczy, Peter; Ganslandt, Oliver; Nagel, Gabriele; Coburger, Jan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background World Health Organization (WHO) grade II low-grade gliomas (LGGs) in adults are rare, and patients' mean overall survival (OS) is relatively long. Epidemiological data on factors influencing tumor genesis and progression are scarce, and prospective data on surgical management are still lacking. Because of the molecular heterogeneity of LGG, a comprehensive molecular characterization is required for any clinical and epidemiological research. Further, a detailed radiologic assessment is needed as the only established objective criterion for progressive disease. Both radiologic and molecular assessments have to be standardized to produce comparable data. The aim of the registry is to improve the evidence for surgical management of LGG patients by establishing a multicenter registry with a strong surgical and clinical focus including mandatory biobanking.Methods The LoG-Glio project is a prospective national observational multicenter registry that began on November 1, 2015. Inclusion criteria encompass all patients > 18 years of age with a radiologic suspicion of LGG. Patients with severe neurologic or psychiatric disorders that may interfere with their informed consent or if there is no possibility for further follow-up are excluded. Diagnosis of glioblastoma WHO grade IV isocitrate dehydrogenase (IDH) wild type leads to a secondary exclusion of patients. In addition to demographic data, results of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire, add-on for patients with brain tumors, and National Health Institute Stroke Scale before and after surgery and during regular follow-ups are collected. At each time point a detailed recording of surgical and adjuvant treatment is performed. Radiologic assessment involves three-dimensional (3D) acquisition of T1, fluid-attenuated inversion recovery, and T2 sequences. For the final evaluation, a central detailed neuropathologic and molecular assessment of tumor samples and a radiologic evaluation of imaging sets are part of the study protocol.Results We report the first 100 consecutively registered patients for LoG-Glio. Three patients dropped out due to loss of follow-up. Of the remaining recruited patients, 8 were classified as wait and scan; 89 had surgery. Using the inclusion criteria described previously, 70 patients had an IDH-mutated glioma, 10 had miscellaneous rare LGGs, and 8 patients had an IDH wild-type WHO grade II or III glioma.Conclusion The LoG-Glio registry has been successfully implemented. Applied selection criteria result in an appropriately balanced patient cohort. Short-term outcome data on epidemiology as well as the influence of current surgical techniques and adjuvant treatment on patient outcomes are expected. In the long run, the aim of the registry is to validate the new molecular-based WHO classification and the influence of the extent of resection on progression-free survival and OS. The registry provides an open platform for future research projects benefiting patients with LGG.
Keywords: low-grade glioma; register; IDH; extent of resection; overall survival; progression-free survival; quality of life